Anisotropic thermally superinsulating boron nitride composite aerogel for building thermal management. (June 2023) - Adegun, Miracle Hope; Chan, Kit-Ying; Yang, Jie; Venkatesan, Harun; Kim, Eunyoung; Zhang, Heng; Shen, Xi; Yang, Jinglei; Kim, Jang-Kyo
Graphical abstract: An anisotropic and lightweight BNNS/PVA composite aerogel is rationally designed using the unidirectional freeze-casting technique. The composite aerogel with optimal BNNS and PVA loadings possesses highly aligned porous channels delivering a combination of ultralow thermal conductivity, very high solar reflectance and thermal emittance in the atmospheric transparency windows. This desired trait makes the composite aerogel a promising candidate for thermal management in buildings and other applications requiring efficient thermal insulation. Highlights: Lightweight composite aerogels with aligned porous channels are fabricated using environmentally friendly materials based on the unidirectional freeze-casting process. The aerogels deliver a combination of ultralow thermal conductivity, high solar-weighted reflectance and high thermal emittance within the atmospheric window, making them ideal for thermal insulation in buildings. The high solar reflectance of 95 % over the whole sunlight wavelength of 0.3–2.5 μm and near unity emittance above 93 % in the atmospheric window range of 8–13 μm enable the composite aerogel to maintain the normal body temperature even under the high solar irradiance. The aerogel is able to maintain about 50 % reduction in cooling energy consumption of a building model. Abstract: Thermally insulating materials are commonly used to reduce energy consumption in buildings. Most commercial products possess only low thermal conductivities but poor insulating capabilities in the daytime with little sunlight reflectance and thermal emittance. It is challenging to achieve all traits in the same material. Herein, anisotropic boron nitride nanosheet (BNNS)/polyvinyl alcohol composite aerogels are developed using the unidirectional freeze-casting technique. Benefitting from the aligned porous structure, the composite aerogel with an optimal BNNS content exhibits a combination of an ultralow TC of 20.3 mW/mK in the through-thickness direction, a high solar-weighted reflectance of 95.0 % over the whole sunlight wavelength and a high emittance of above 93 % within the atmospheric transparency window. These exceptional thermo-optical properties enable the composite aerogel to maintain the interior temperature much cooler than commercially available foams, making them promising candidates as superinsulating envelopes for energy saving in buildings towards carbon neutrality.